Cellular repressor of E1A-stimulated gene overexpression in bone mesenchymal stem cells protects against rat myocardial infarction. (15th March 2015) - Peng, Chengfei; Pei, Haifeng; Wei, Feipeng; Tian, Xiaoxiang; Deng, Jie; Yan, Chenghui; Li, Yang; Sun, Mingyu; Zhang, Jian; Liu, Dan; Rong, Jingjing; Wang, Jie; et al.
Abstract: Background: Bone mesenchymal stem cell (BMSC) therapy has modest success in ischemic heart disease but has been limited by poor survival in diseased microenvironments. Cellular repressor of E1A-stimulated genes (CREG) can prevent BMSCs from apoptosis in vitro ; however, the effects of CREG-modified BMSCs on ischemic heart disease and the related mechanism remain undefined. Therefore, we designed to study the cardioprotective effects of CREG overexpression in BMSCs ( CREG BMSCs) after transplantation into infarcted heart of rats. Methods: In vivo studies, 50 μl PBS or 1.5 × 10 6 Norm BMSCs, GFP BMSCs or CREG BMSCs were implanted intramyocardially in myocardial infarction rat models. 3 or 14 days later, cardiac function, fibrosis, apoptosis and angiogenesis were analyzed by echocardiography, masson, western blot and immunofluorescence staining, respectively. ELISA, western blot and matrigel assay were used in vitro to detect vascular endothelial growth factor (VEGF) secretion, signaling molecule expression, and angiogenic tube formation. Results: In vivo, prolonged cardiac function (14d LVEF: 50.87 ± 0.94%; LVFS: 23.41 ± 1.12%), decreased fibrosis (14d Fibrotic area: 27.37 ± 1.03%) and apoptosis and increased angiogenesis were observed in CREG BMSCs, compared with other groups. In vivo and in vitro, VEGF secretion from CREG BMSCs was markedly enhanced. In vitro, angiogenic tube formation in CREG BMSC supernatants significantly increased. Moreover, CREG activated hypoxia-inducible factor-1α (HIF-1α), but not HIF-1β. Knockdown of HIF-1α with siRNA decreased VEGF secretion and angiogenic tube formation. Notably, CREG did not influence HIF-1α mRNA synthesis but inhibited the expression of Von Hippel–Lindau (VHL), a key protein that regulates HIF-1α degradation. Conclusions: The CREG BMSC transplantation, directly or indirectly, may promote VEGF's anti-apoptosis and angiogenesis via the inhibition of VHL-mediated HIF-1α degradation, consequently protecting against myocardial infarction.